Dental composites: a review. - Talib, R. (1993)
Dental composite resins are widely used in dental practice and are continually being developed in order to obtain better products. To gain full benefit from these materials, it is important for the clinician to understand their properties. The following is a review of the more common characteristics of composites in current use.